Model Pendampingan Adaptif dalam Implementasi Sistem Penjaminan Mutu Internal (SPMI) di Sekolah Kepulauan di SMP Negeri 15 Ambon - Rumfot, Sumarni; Sohilait, Desembra; Untayana, Adha (Universitas Pattimura, 2025)
This community service initiative stems from the need to implement an Internal Quality Assurance System (SPMI) as a foundation for educational quality improvement, particularly in island regions such as Ambon with limited resources and supervision access. The program aimed to enhance teachers’ and principals’ capacities in understanding, applying, and developing the PPEPP cycle (Establishment, Implementation, Evaluation, Control, and Improvement) independently and sustainably. The activity was conducted in five public junior high schools over six months, involving 45 participants comprising teachers and principals. The method involved participatory training, technical mentoring, and collaborative evaluation between universities, schools, and local government. Results indicated significant improvement in quality management competence and the establishment of a strong quality culture. This activity developed an adaptive mentoring model grounded in local collaboration, effective for island-based schools. The recommendation emphasizes continuous mentoring policy and integration of digital-based quality systems